An experimental study on steel-encased buckling restrained brace hysteretic dampers. - Eryasar, Mehmet Emrah
This paper describes a seismic test program performed on 12 steel encased buckling restrained braces (BRBs). The use of rolled or built up buckling restraining mechanisms with welded or bolted attachments was examined. In addition, the effects of bolt pretension, core to encasing attachment details, aspect ratio of core segment and imperfections due to manufacturing on the brace response were investigated. All specimens were subjected to a stepwise incremental quasi static testing protocol with a maximum axial strain amplitude of 2 percent. All specimens except one showed satisfactory performance with stable hysteretic response and sustained cumulative inelastic deformations in excess of 200 times the yield deformation. Based on the experimental results, the compression strength adjustment factor and the strain hardening adjustment factor for each excursion were quantified. Test resuls revealed that these two factors are significantly influenced by the parameters investigated in the experimental program. BRB details were also found to influence the buckling and the yielding patterns of the core segment.
Keywords: Buckling restrained brace; Hysteretic damper; Energy dissipation; Friction; Yielding; Seismic